Uncertainty Analysis of Reactor Structure Material Activation Calculation Induced From Nuclear Data - Jiebo, Wu; Chao, Yang; Tao, Yu; Zhenping, Chen (Frontiers in Energy Research, 2022)
Highly accurate activation calculations are the basis of radiation protection optimization design, and the accuracy of activation calculations depends on nuclear data. Based on the ENDF/B-VIII.0 and JEFF3.3 decay evaluation libraries, the influence of different nuclear data on the reactor structural material activation calculation is analyzed, and the nuclear data-related sensitivity and uncertainty quantification of radioactivity, decay heat and photon sources are carried out by the global sensitivity analysis method and the Latin Hypercube Sampling method. Based on uncertainty data in ENDF/B-VIII.0 and JEFF3.3, quantifying the uncertainty of radioactivity, decay heat and photon source in the shutdown dose calculation of reactor structural materials, the maximum uncertainty of radioactivity and decay heat reach 4.54% and 1.45%, respectively. The half-life and decay energy of 55Fe are the main sources of uncertainty.